Complementarity of direct detection experiments in search of light Dark Matter. Issue 10 (1st October 2022) - Angevaare, J.R.; Bertone, G.; Colijn, A.P.; Decowski, M.P.; Kavanagh, B.J.
Abstract: Dark Matter experiments searching for Weakly interacting massive particles (WIMPs) primarily use nuclear recoils (NRs) in their attempt to detect WIMPs. Migdal-induced electronic recoils (ERs) provide additional sensitivity to light Dark Matter with 𝒪(GeV/ c 2 ) masses. In this work, we use Bayesian inference to find the parameter space where future detectors like XENONnT and SuperCDMS SNOLAB will be able to detect WIMP Dark Matter through NRs, Migdal-induced ERs or a combination thereof. We identify regions where each detector is best at constraining the Dark Matter mass and spin independent cross-section and infer where two or more detection configurations are complementary to constraining these Dark Matter parameters through a combined analysis.